THE EFFECT OF SHADOWING TECHNIQUE ON STUDENTS’ SPEAKING FLUENCY AND PRONUNCIATION ACCURACY - Sari, Dewi Kartika; Jaya, Aswadi (English Community Journal, 2025)
Speaking fluency and pronunciation accuracy are essential components of oral proficiency in English language learning, especially in English as a Foreign Language (EFL) contexts. This study aims to investigate the effect of the shadowing technique on students’ speaking fluency and pronunciation accuracy in English language learning. The participants consisted of 32 eleventh-grade students from a senior high school in Palembang. The research employed a pre-experimental design with a one-group pretest-posttest approach. The instrument used was a speaking test conducted before and after the implementation of the shadowing technique to measure students' improvement. The statistical analysis revealed a significant increase in scores between the pre-test and post-test. The mean pre-test score of 5.06 increased to 8.81 in the post-test, with a significance value (Sig. 2-tailed) of 0.000, indicating a statistically significant effect. These findings demonstrate that the shadowing technique is effective in enhancing students’ speaking fluency and pronunciation accuracy. Therefore, this technique is recommended as a practical method for improving speaking skills in English as a Foreign Language (EFL) classrooms.